2008
DOI: 10.1158/1055-9965.epi-08-0032
|View full text |Cite
|
Sign up to set email alerts
|

Serum Organochlorine Pesticide Residues and Risk of Testicular Germ Cell Carcinoma: A Population-Based Case-Control Study

Abstract: Testicular germ cell carcinoma (TGCC) is the most common malignancy among men ages 20 to 34 years. Although the pathogenesis of TGCC is poorly understood, suboptimal androgen levels or impaired androgen signaling may play a role. Some persistent organochlorine pesticides commonly found in human tissue possess antiandrogenic properties. We examined whether the risk of TGCC is associated with serum levels of 11 organochlorine pesticides, including p,p ¶-DDE, and whether the p,p ¶-DDE-TGCC association is modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 46 publications
2
63
1
Order By: Relevance
“…Biggs et al, (2008) found no evidence that the risk of TC was associated with serum DDE. Recently, a hospital-based case-control study conducted in Italy found that TC patients had elevated concentrations of p,p -DDE (Giannandrea et al, 2011).…”
Section: Dichloro-diphenyl-trichloroethylene (Pp'-dde)mentioning
confidence: 89%
See 2 more Smart Citations
“…Biggs et al, (2008) found no evidence that the risk of TC was associated with serum DDE. Recently, a hospital-based case-control study conducted in Italy found that TC patients had elevated concentrations of p,p -DDE (Giannandrea et al, 2011).…”
Section: Dichloro-diphenyl-trichloroethylene (Pp'-dde)mentioning
confidence: 89%
“…Only one study has examined whether the TC risk associated with hormonally active compounds was modified by androgen receptor CAG. It found no evidence that the risk of TC associated with p,p'-DDE was modified by the number of CAG repeats (Biggs et al, 2008). Several published case-control studies found that longer CAG repeats were associated with risk of nonseminoma.…”
Section: Polymorfism In Genes Involved In Sex Hormone Metabolismmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the case mothers in that study had significantly higher levels of cis-nonachlor, trans-nona chlor, and the sum of chlordanes compared with control mothers, suggesting that the ante natal period may be a particularly important time window of exposure for influencing TGCT development. No associations with chlordane congeners were observed in the Washington State study (Biggs et al 2008). The biologic basis for a chlordane effect on TGCT develop ment is unclear.…”
Section: Discussionmentioning
confidence: 77%
“…The U.S. Servicemen's Testicular Tumor Environmental and Endocrine Determinant (STEED) Study, a large case-control investigation of TGCTs (754 cases, 928 controls) conducted among U.S. servicemen, similarly found elevated prediagnostic concentrations of cis-nonachlor, trans-nonachlor, and the insecticide metabolite p,p´-dichlorodiphenyldichloroethylene (p,p´-DDE) among cases versus controls (McGlynn et al 2008). However, a recent population-based study (246 cases, 630 controls) conducted in Washington State observed no evidence of association with OC compounds (Biggs et al 2008). Findings from studies of cryptorchidism and hypospadias do not support an association with OC compounds (Bhatia et al 2005;Damgaard et al 2006;Flores-Luevano et al 2003;Longnecker et al 2002;Waliszewski et al 2005).…”
Section: Researchmentioning
confidence: 97%